﻿Les Vite de 1672 de Bellori : hypothèses de reconstitution du programme iconographique et théorique - Lhote, Jean-François (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 1987)
This article presents the evidence for a tentative reconstruction of the theoretical and iconographic programme of Bellori’s Vite. The author seeks to show that Bellori’s biographies are arranged according to a programmatic scheme probably conceived in the late 1630s or early 1640s, during the biographer’s youth, and that this programme is inspired by Lomazzo’s Temple of Painting and the theory of Governors.Published in 1672, the Vite present the lives of twelve artists, following—up to a point—the chronological order of their deaths, as was the rule in that literary genre. However, three of them (Annibale Carracci, Caravaggio, and Domenichino) are out of chronological order, and at the same time divide the whole group into three equal parts. This anomaly is explained by a poem published in 1642 by the young Bellori (as a preface to Baglione’s Vite de’Pittori) in which he classified modern artists according to the scheme of the three Graces. In the poem, Bellori devoted a complete strophe to each of the artists he would choose as “governors” thirty years later, describing his particular genius and relating him to one of the Graces.The same kind of classification was used by the poet Antonio Bruni, who in Le Tre Gratie (1630) divided poetry into three broad categories: lyric, heroic, and moral and sacred. Each of these categories is governed by one of the Graces. Bruni asserts that his aim is to classify poetry with greater clarity and avoid the confusion generated by the mixture of different genres in a single poem.A study of the emblematic etchings that precede the biographies confirms this analysis. Apparently the Idea, which was to become so famous in European academies of art, was added to the work very late, almost at the moment of printing. This late addition was the cause of some confusion at the printer’s desk, with the result that this etching was misplaced in the text. Nevertheless the scheme of the programme appears very clearly. The three governors are associated with three concepts: Theoria, Praxis, and Conceptus-Imaginatio. The other three etchings in each group are related to the main theme and explain it. This figurative complement to the biographies testifies to the importance and vitality of such figurative and theoretical sources as Testa’s Liceo della Pittura, also designed in the late 1630s.The iconographic analysis of the etchings shows that Bellori apparently adhered closely to the three-level educational programme defined by Testa for the perfect painter, seeking at the same time to reconcile schools and styles of the modern period in his Ideal Temple of Painting. Despite what has often been said, it was not his intention to oppose Poussin to Caravaggio, nor did he aim to write mere biographies of individuals.